(untitled) (Journal of Science and Technology, 2016)
Secamone afzelii has been used traditionally for wound healing. To confirm the fokloric uses of the plant, the methanol extract of the plant was tested for antimicrobial and antioxidant activities, since antimicrobial agents and antioxidants facilitate wound healing. The extract showed some level of antimicrobial and antioxidant activities. The selective antimicrobial and significant antioxidant activities suggest that the folkloric use of the plant as a wound healing may be based on the antimicrobial and antioxidant roles.